The role of nationality and hotel class on guests' satisfaction: A fuzzy-TOPSIS approach applied in Saint Petersburg - Juan Carlos Martín; Veronika Rudchenko; María-Victoria Sánchez-Rebull (Administrative Sciences, 2020)
Although hotels usually have clients from different nationalities, the research analyses the multicultural effects on hotel customers' satisfaction is still scant. This paper aims to contribute to the realm of hotel management by providing interesting managerial insights into how different nationalities perceive hotel attributes differently using two hotels located in Saint Petersburg as a case study. To that end, a fuzzy hybrid method based on the technique of similarity to ideal solution (FTOPSIS) is proposed. The results are based on a sample of 447 guests and show that: (1) nationality influences the hotel guests' satisfaction; (2) customers are, in general, more elastic in three-star hotels than in four-star hotels; (3) welcome gifts in the room and in the bathroom are key attributes in the clients' satisfaction; and (4) Italian and Spanish guests are the least and the most satisfied customers, respectively. The study offers a number of important managerial insights to hotel managers and practitioners. The average figures obtained by general hotel satisfaction surveys usually hinder important peculiarities that need to be addressed when managers develop strategic satisfaction enhancement programmes. In particular, our results show that managers need to adapt the programmes to the differences observed by nationalities.
Keywords: 350; fuzzy numbers; guest nationality; hotel guests' satisfaction; key hotel attributes; multicultural analysis; TOPSIS